2013
DOI: 10.1051/epjconf/20135901005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on shock ignition targets for inertial fusion energy

Abstract: Abstract. Shock-ignited inertial fusion targets are studied by one dimensional and two-dimensional numerical simulations. Most of the study refers to the simple all-DT HiPER baseline target (imploded mass of 0.29 mg); both the reference laser wavelength = 0.35 m, and = 0.25 m are considered. The target achieves 1D gain about 80 (120) with total laser energy of 260 kJ (180 kJ) at = 0.35 m (0.25 m). Operating windows for the parameters of the laser ignition spike are described. According to preliminary simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…High-resolution simulations including modes from 2 to 256 induced by nominal (expected) target surface perturbations and laser imprint [43] have shown that the final low-mode asymmetries can be large enough to quench ignition. Asymmetries of this level, just large enough to prevent ignition, can be remedied by increasing the ignitor spike power [43,88,95]. The stronger shock then provides enough hot spot energy to ignite the target, although the gain drops.…”
Section: Two-dimensional Effects: Short-wavelength (High-mode) Instab...mentioning
confidence: 99%
“…High-resolution simulations including modes from 2 to 256 induced by nominal (expected) target surface perturbations and laser imprint [43] have shown that the final low-mode asymmetries can be large enough to quench ignition. Asymmetries of this level, just large enough to prevent ignition, can be remedied by increasing the ignitor spike power [43,88,95]. The stronger shock then provides enough hot spot energy to ignite the target, although the gain drops.…”
Section: Two-dimensional Effects: Short-wavelength (High-mode) Instab...mentioning
confidence: 99%
“…This makes them sensitive to long-scale asymmetries, resulting, e.g. from target mispositioning, as was shown in [14,31]. Sensitivity to mispositioning (and presumably to other sources of longscale perturbations) depend on target safety factors, as will be discussed in section 6.…”
Section: Target Designmentioning
confidence: 91%
“…Sensitivity to mispositioning (and presumably to other sources of longscale perturbations) depend on target safety factors, as will be discussed in section 6. Instead, fluid simulations (either with flux-limited electron thermal conductivity [13,14,31] or with non-local electron transport [50]) indicate that large spike asymmetries are tolerated, probably due to thermal smoothing in the rather thick thermal conduction layer between the critical radius and ablation front at the time of spike irradiation. According to the above studies, SI can achieve high gain at a laser energy and power achievable on the operating NIF facility [5] and on the LMJ facility [10], currently under construction.…”
Section: Target Designmentioning
confidence: 99%
See 2 more Smart Citations